Transit ring: bubble flow control for eliminating inter-ring communication congestion - Ouyang, Yiming; Sun, Chenglong; Li, Ruifeng; Wang, Qi; Li, Jianhua (The Journal of supercomputing, 2023)
Bubble flow control is a flow control mechanism commonly used in torus network. Bubble flow control ensures the orderly flow of packets in the ring by efficiently allocating intra-ring buffer resources and solves the intra-ring deadlock problem. However, inter-ring communication with bubble flow control is subject to strict limitations. When packets are communicated across the rings, starvation may occur, resulting in prolonged blocking within the ring. Inefficient inter-ring communication not only generates Head-of-Line blocking, but also affects the whole intra-ring communication through the backpressure mechanism. We propose a Transit Ring design that establishes an alternate ring link in the torus network by reusing free buffers in the router. By evacuating packets blocking inter-ring communication into the Transit Ring, starvation, as well as Head-of-Line blocking, in the network is eliminated. Compared to state-of-the-art bubble flow control, our proposed design improves saturation throughput by an average of 15.9% in a 4 × 4 torus network and 17.06% in an 8 × 8 torus network.